Unleashing the Power of Networks - Case Study - Guillermo Velasquez; Peggy Odem (Journal of Systemics, Cybernetics and Informatics, 2007)

(untitled)
As market forces continue to push the envelope of productivity and performance, developing a well-trained and highly skilled work force is considered one of the most important business differentiators in the market place. A recent survey1 indicates that informal training accounts for over 70% of all the training an individual gets in his/her job. These data emphasize the importance of having a training system in place that can fulfill the needs of the work force in a timely manner. Halliburton Energy Services has developed a system of communities of practice to strengthen organizational and individual development. This paper discusses how this training system is transforming the culture and the way it does business.